PENGARUH INTERACTIVE FLAT PANEL, METODE PEMBELAJARAN INTERAKTIF, DAN MOTIVASI BELAJAR TERHADAP KEAKTIFAN DAN MINAT BELAJAR SISWA SD MUTU DI KEDUNGDEM KABUPATEN BOJONEGORO - Intan Nuraini, Dea; Ayu Wulandari, Nadia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low levels of students’ motivation, activeness, and learning interest remain a major issue in elementary school learning processes, particularly in classrooms with limited interactive activities. This study aims to analyze the effect of interactive learning media and interactive learning methods on students’ learning motivation and its implications for students’ activeness and learning interest at SD Mutu Kedungadem, Bojonegoro Regency. This research employed a quantitative approach using a simple experimental and survey method. Data were collected through pretest and posttest, learning motivation questionnaires, and observations of students’ activeness. The data were analyzed using descriptive quantitative analysis and simple statistical analysis. The results showed that the average posttest scores were higher than the pretest scores after the implementation of interactive learning media. Furthermore, statistical analysis indicated that learning motivation had a significant effect on students’ activeness, contributing 17.53%. These findings suggest that the use of interactive learning media, such as Interactive Flat Panels, supported by interactive learning methods can enhance students’ motivation, activeness, and learning interest. In conclusion, the integration of interactive learning media and methods is an effective strategy to improve the quality of learning in elementary schools.